HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP TINDAKAN MEROKOK DI SMA NURUL FALAH PEKANBARU TAHUN 2018 - Hamidah sari Batubara (Jurnal Indragiri Penelitian Multidisiplin, 2022)
70 % mortality rate by cigarettes that occur in developing countries . Smoking is one of the biggest causes of death in the world. In Indonesia, cigarette user numbers of men and women around ( 54.59 % ). The content that contained in cigarettes are: nicotine, lead, gas monoxide, tar, ammonia, then the effects that occur in a smoker namely : impact on lungs, heart, and reproductive system. Women who smoke risk of interruption of pregnancy, abortion, and conginetal malformations. This study aims to determine the relationship of knowledge and attitudes of young women towards the act of smoking in high school Nurul Falah Pekanbaru 2014. Present study is cross-sectional quantitative analytic design that uses random sampling techniques sympel. The study was conducted using a sample of 60 questionnaires to teenagers in high school Nurul Falah Pekanbaru 2018. And analyzed using univariate and bivariate chi-square test with software (SPSS for Windows) with a 90 % degree of confidence. From the results of the univariate analysis there are 45 people (75 %) of teenagers who have high knowledge , and 6 (13.3 %) of them is smoking. Then from 53 people (88.3 %) were positive , and 10 people (18.9 %) of them is smoking. From the results of chi-square test showed that any relationship between the knowledge and the act of smoking. Cause p value < a that is 0.062 < 0.1 and no relationship attitude towards the act of smoking as p value > a that is 0.619 > 0,1. Therefore it is recommended to teenagers to increase the knowledge and be careful in choosing your friends in order to avoid the things that affect to act of smoking.